The Effect of Hyperbaric Oxygen Therapy on Neutrophil to Lymphocyte Ratio (NLR) in Wistar Strain Female White Rats (Rattus norvegicus) Induced by 7,12-dimethylbenz[a]anthracene (DMBA) - Mangkuluhur, Ande; Sudiarta, Ketut Edy; Nefertiti, Eva Pravitasari (Indonesian Journal of Cancer, 2026)
Background: Tumors are caused by uncontrolled cell growth, and the immune system plays a crucial role in this process. Neutrophils and lymphocytes are key immune cells involved in tumor behavior. Adenosine and its A2 receptor can activate neutrophils to promote inflammation that may lead to tumor growth. In contrast, lymphocyte especially cytotoxic T cells, can attack and kill tumor cells, helping to reduce tumor growth and inflammation. This study explores how hyperbaric oxygen therapy (HBOT) can influence the neutrophil-to-lymphocyte ratio (NLR) in female Wistar rats exposed to a known carcinogen, 7,12- dimethylbenz[a]anthracene (DMBA).Method: The research followed a post-test-only control group design. Two control groups were established: one that received a normal diet and the other that was treated with DMBA at a dosage of 20 mg/kgBW for four weeks. The treatment group received both the carcinogen and HBOT at 1.7 Atmospheric Absolute for 30 minutes, three times daily for five days. Blood samples were taken, and the NLR was measured using IBM SPSS software version 26. Result: Results showed significant differences in NLR among the groups. The negative control group had a mean NLR of 1.3444, the positive control group had 3.7889, and the treatment group had 1.6889. A statistically significant difference in these mean NLR values (p = 0.000) was observed among Female Wistar Rats subjected to the effects of the carcinogen DMBA combined with HBOT. Conclusion: The study concluded that HBOT significantly reduced NLR values in these rats exposed to the carcinogen. These findings highlight the potential of HBOT as a supportive therapeutic intervention in modulating the tumor-associated immune environment.